A chemist's guide to density functional theory. (2nd ed.) - Koch, Wolfram. ; Holthausen, Max C. (Wiley-VCH, 2020)
The Definition of the Model --|tElementary Quantum Chemistry --|tThe Schrodinger Equation --|tThe Variational Principle --|tThe Hartree-Fock Approximation --|tThe Restricted and Unrestricted Hartree-Fock Models --|tElectron Correlation --|tElectron Density and Hole Functions --|tThe Electron Density --|tThe Pair Density --|tFermi and Coulomb Holes --|tThe Fermi Hole --|tThe Coulomb Hole --|tThe Electron Density as Basic Variable: Early Attempts --|tDoes it Make Sense? --|tThe Thomas-Fermi Model --|tSlater's Approximation of Hartree-Fock Exchange --|tThe Hohenberg-Kohn Theorems --|tThe First Hohenberg-Kohn Theorem: Proof of Existence --|tThe Second Hohenberg-Kohn Theorem: Variational Principle --|tThe Constrained-Search Approach --|tDo We Know the Ground State Wave Function in Density Functional Theory? --|tThe Kohn-Sham Approach --|tOrbitals and the Non-Interacting Reference System --|tThe Kohn-Sham Equations --|tThe Kohn-Sham Potential is Local --|tThe Exchange-Correlation Energy in the Kohn-Sham and Hartree-Fock Schemes --|tDo the Kohn-Sham Orbitals Mean Anything? --|tIs the Kohn-Sham Approach a Single Determinant Method? --|tThe Unrestricted Kohn-Sham Formalism --|tOn Degeneracy, Ensembles and other Oddities --|tExcited States and the Multiplet Problem --|tThe Quest for Approximate Exchange-Correlation Functionals --|tIs There a Systematic Strategy? --|tThe Adiabatic Connection --|tFrom Holes to Functionals --|tThe Local Density and Local Spin-Density Approximations --|tThe Generalized Gradient Approximation --|tHybrid Functionals --|tSelf-Interaction...